Risk Factors Related to Death of Tuberculosis Patients in Ciparay Health Center Bandung District Year 2022-2024 - Zaelani, Ahmad; Nurjamilatunnisa, Nurjamilatunnisa; Resmawati, Resmawati; Berliana Tania Fidzikri, Nanda (Rifa'Institute, 2025)
All over the world there must be an infectious and deadly disease, namely tuberculosis, which has many risk factors including, socioeconomics, education, age, income, gender, smoking habits, home environment conditions, making contacts and many others, the purpose of this study is to find out what factors are associated with the death of tuberculosis patients in the Ciparay Health Center, Bandung Regency, Case control is a research design used in this study assisted by questionnaires for data collection techniques, in this study as many as 82 respondents were involved as respondents, in this study the analysis used to multivariate and use binary logistic regression test, the results of this study the risk of death of tuberculosis patients is smoking with an odds ratio value (p=0.024, OR 7.273, and 95%CI: 1.298-40.757) if it is concluded that tuberculosis patients who are smokers will be at risk 7 times to experience death compared to tuberculosis patients who are not smokers, therefore it is immediately to stop smoking activities for tuberculosis patients, besides that there are other types of variables, namely the physical condition of the house (p=0.008), comorbidities in tuberculosis patients (p=0.006), gender (p=0.013), history of tuberculosis (p=0.010), and BCG immunization (p=0.002).